The behaviour of sea snakes (Emydocephalus annulatus) shifts with the tides - Claire Goiran (Nature Portfolio, 2020)
Abstract Tidal cycles are known to affect the ecology of many marine animals, but logistical obstacles have discouraged behavioural studies on sea snakes in the wild. Here, we analyse a large dataset (1,445 observations of 126 individuals) to explore tidally-driven shifts in the behaviour of free-ranging turtle-headed sea snakes (Emydocephalus annulatus, Hydrophiinae) in the Baie des Citrons, New Caledonia. Snakes tended to move into newly-inundated areas with the rising tide, and became more active (e.g. switched from inactivity to mate-searching and courting) as water levels rose. However, the relative use of alternative habitat types was largely unaffected by tidal phase.